The prevalence and clinical course of HIV-associated pulmonary cryptococcosis in Uganda - Yoo, Samuel D.; Worodria, William; Davis, J. L.; Cattamanchi, Adithya; Boon, Saskia den; Kyeyune, Rachel; Kisembo, Harriet; Huang, Laurence (Journal of acquired immune deficiency syndromes, 2010)
The prevalence and clinical course of pulmonary cryptococcosis in Sub-Saharan Africa are not well-described. Methods—Consecutive HIV-infected adults hospitalized at Mulago Hospital (Kampala, Uganda) between September 2007 and July 2008 with cough ≥ 2 weeks were enrolled. Patients with negative sputum smears for acid-fast bacilli were referred for bronchoscopy with bronchoalveolar lavage (BAL). BAL fluid was examined for mycobacteria, Pneumocystis jirovecii, and fungi. Patients were followed two and six months after hospital discharge. Results—Of 407 patients enrolled, 132 (32%) underwent bronchoscopy. Of 132 BAL fungal cultures, 15 (11%) grew Cryptococcus neoformans. None of the patients were suspected to have pulmonary cryptococcosis on admission. The median CD4 count among those with pulmonary cryptococcosis was 23 cells/μL (IQR 7–51). Of 13 patients who completed six-month follow-up, four died and nine were improved, including five who had started antiretroviral therapy (ART) but had not received antifungal medication. Conclusions—Pulmonary cryptococcosis is common in HIV-infected TB suspects in Uganda. Early initiation of ART in those with isolated pulmonary infection may improve outcomes, even without anti-fungal therapy. This finding suggests that some HIV-infected patients with C. neoformans isolated from respiratory samples may have colonization or localized infection.
Keywords: Pulmonary Cryptococcosis; HIV/AIDS; Bronchoscopy